2003
DOI: 10.1111/j.1945-5100.2003.tb01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Noble gases and cosmogenic radionuclides in the Gold Basin L4 chondrite shower: Thermal history, exposure history, and pre‐atmospheric size

Abstract: Ar concentrations indicate a major impact on the parent body between 300 and 400 Myr ago, which must have preceded the impacts that brought the Gold Basin meteoroid to the surface of the parent body and then expelled it from the parent body 18 Myr ago.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(100 citation statements)
references
References 45 publications
10
86
4
Order By: Relevance
“…The most remarkable observation is that the 10 Be and 26 Al concentrations are not correlated, but seem to vary randomly, with 26 Al/ 10 Be ratios ranging from ~3.5 to ~5.0. These 26 Al/ 10 Be ratios are significantly higher than typical 26 Al/ 10 Be production rate ratios of 3.0-3.5 in large chondrites (Vogt et al 1992;Welten et al 2003). The high 26 Al/ 10 Be ratios in JaH 073 indicate that 10 Be and (to a lesser extent) 26 Al were not saturated at the time of fall.…”
Section: Radionuclidesmentioning
confidence: 83%
See 4 more Smart Citations
“…The most remarkable observation is that the 10 Be and 26 Al concentrations are not correlated, but seem to vary randomly, with 26 Al/ 10 Be ratios ranging from ~3.5 to ~5.0. These 26 Al/ 10 Be ratios are significantly higher than typical 26 Al/ 10 Be production rate ratios of 3.0-3.5 in large chondrites (Vogt et al 1992;Welten et al 2003). The high 26 Al/ 10 Be ratios in JaH 073 indicate that 10 Be and (to a lesser extent) 26 Al were not saturated at the time of fall.…”
Section: Radionuclidesmentioning
confidence: 83%
“…To compare the results with model calculations we thus normalize all 10 Be and 26 Al results to bulk L-chondrites, using the normalization factors, F10 and F26, given in Table 3. Although the variations in 10 Be and 26 Al are small compared to those (factors of [15][16][17][18][19][20] found in the large Gold Basin Lchondrite shower (Welten et al 2003), they are significantly larger than those found in Frontier Mountain (FRO) 90174, an Antarctic H-chondrite shower with a pre-atmospheric radius of 80-100 cm (Welten et al 2001). The most remarkable observation is that the 10 Be and 26 Al concentrations are not correlated, but seem to vary randomly, with 26 Al/ 10 Be ratios ranging from ~3.5 to ~5.0.…”
Section: Radionuclidesmentioning
confidence: 99%
See 3 more Smart Citations